Phenomenological model for determining velocity field of LPG jet in combustion chamber of direct injection S.I. engine - Ga, Bui Van; Tho, Phung Xuan; Quang, Nhan Hong; Huong, Nguyen Huu (Vietnam Journal of Mechanics, 2004)
A phenomenological model has been established to predict the velocity distribution of LPG (Liquefied Petroleum Gas) jet in combustion chamber of spark ignition (SI) engine. A shaped coefficient \(β\) governing the similarity of velocity profiles of LPG jets has been defined based on the theoretical and experimental analyses of turbulent diffusion jets. The results show that \(β\) is constant for steady jet but it is not the case for unsteady one. The model will enable us to calculate the velocity profiles of LPG jet after ending injection. This is necessary for research of stratified combustion in direct injection LPG SI engines.